Precipice eaudiobook A novel. - Harris, Robert (HarperAudio, 2024)
"Robert Harris is, simply put, masterful."—Karin Slaughter A spellbinding novel of passion, intrigue, and betrayal set in England in the months leading to the Great War from the bestselling author of Act of Oblivion, Fatherland, The Ghostwriter, and Munich. Summer 1914. A world on the brink of catastrophe. In London, twenty-six-year-old Venetia Stanley—aristocratic, clever, bored, reckless—is part of a fast group of upper-crust bohemians and socialites known as "The Coterie." She's also engaged in a clandestine love affair with the Prime Minister, H. H. Asquith, a man more than twice her age. He writes to her obsessively, sharing the most sensitive matters of state. As Asquith reluctantly leads the country into war with Germany, a young intelligence officer with Scotland Yard is assigned to investigate a leak of top-secret documents. Suddenly, what was a sexual intrigue becomes a matter of national security that could topple the British government—and will alter the course of political history. An unrivaled master of seamlessly weaving fact and fiction, Precipice is another electrifying thriller from the brilliant imagination of Robert Harris.